Examining the communication model of customer participation and competitive business with social media based on brand in manufacturing and trading companies - javad mashhadizadeh; Farzad Karimi; Mojtaba aghajani (ارزش آفرینی در مدیریت کسب و کار)
AbstractThe purpose of this research is to investigate the communication model of customer participation and competitive business with social media based on brand in manufacturing and trading companies of Ahvaz city. In terms of purpose, the current research is applicable, and of the survey research type. The statistical population of the research includes the customers of the food manufacturing and trading companies in the industrial towns of Ahvaz city. Due to the unlimited population, the statistical sample was considered to be 384 people using Cochran's formula, and finally 312 questionnaires were analyzed. Sampling in this research is available randomly. The collection tool in this research is a questionnaire. Data analysis was done using SPSS and PLS software. The findings showed that the identified factors had a significant effect, and the overall index of fit (GOF) was obtained as 0.661, which is a strong index and shows the overall high quality of the model.Extended Abstract                                           IntroductionVirtual social networks are a new generation of Internet websites. Internet users in these websites gather together virtually around a shared axis and form online communities (Torki et al, 2023). With the spread of the Internet and the spread of social media, customers' buying patterns have changed and their shopping habits have been affected by business based on social networks. In addition to using search engines, customers also search for desired products and brands on social media such as Instagram. The growth of Instagram has attracted the interest of many large companies that are looking for new ways to strengthen their relationships with their customers. Instagram is one of the fastest programs in growing social media (Anderson Jiang, 2018).Consumer interactions on social media are generally important. The evolution of social media and technologies now allow consumers to easily share their opinions through the online environment. Written and visual content sharing programs allow users to share information resulting from the hedonistic activities resulting from the use of various products and services (Fox et al, 2018).Online branding is becoming increasingly popular in modern society, as marketing is largely developed through social media platforms, blogs, websites, and other online channels. Companies should also have an active digital presence and show themselves in the digital field by using different digital channels to develop the brand (Bamm et al, 2018). These activities usually require high or moderate participation from consumers, which creates a positive psychological state when experiencing their participation or cooperation with the brand, and includes aspects of cognitive effort, emotional involvement, and behavioral diversity (Lu et al, 2015).For this purpose, the current research aims to answer this question: What is the communication model of customer participation and competitive business with social media based on brand in manufacturing and trading companies of Ahvaz?Theoretical FrameworkbrandA brand is not only a symbol that distinguishes a product from others, but also includes all the features that come to mind when a buyer thinks of that brand. These characteristics are the concrete, abstract, psychological, and social characteristics of that product (Meysamiazad et al, 2024).social mediaSocial media is a group of online user programs whose purpose is to facilitate interactions and content sharing. Social media is a group of Internet-based applications that are built on the ideological basis of Web 2 technology and allow users to create and share their own content. People increasingly consider social media programs to be an important part of their daily lives and are more likely to move their interactions to virtual programs (Alalwan et al, 2017).Competitive advantage and customer engagementThe brand can create a competitive advantage for the company and maintain loyal customers. Creating a positive brand image is a strategy. This brand image can be considered as a cultural heritage, service quality, and trust; and can affect customer satisfaction (Araujo et al, 2023). Wang & Kim (2017) showed that functional advantages in products, service advantage in providing services, analytical advantage in CRM, multi-channel advantage in communication, symbolic advantage in advertising, and network advantage in sharing resources have a significant impact on customer value and brand loyalty.Competitive advantage of online businessesCompanies in the market look for mistakes of competitors and use opportunities. One of the ways to increase the power of competition in this market is to use strategic management in order to achieve a competitive advantage. In the most basic concept of competitive advantage, in a way, it refers to the company's exploitation of resources in order to achieve superior performance in which three main factors can lead to differentiation and difference from other competitors. These three factors include sources of competitive advantage, competitive advantage, and company performance. Competitive advantage is the basis of strategic planning in companies, which broadly refers to using opportunities and neutralizing competitive threats (Tong, 2023).Torki et al, (2023) investigated the impact of social media participation on green management (case study of employees of Shahrekord industrial companies). The results showed that the amount of use of social media, the type of use of social media, and the amount of trust in users in social media have a positive effect on green management. This means that with people's easy access to virtual space and social networks, the Internet has become an inseparable part of life. In order to make optimal use of the created space, companies are trying to use this opportunity optimally and to their advantage, and improve the green management.Rahimi et al, (2023) investigated the impact of digital content marketing on brand awareness through social media and customer interaction. The results showed that there is a positive and significant relationship between digital content marketing and brand awareness. Also, social media and customer interaction play a significant mediating role in the relationship between digital content marketing and brand awareness. It is obvious that digital content marketing as a new phenomenon plays a vital role in displaying brand name, strengthening customer relationship and increasing brand awareness, customer loyalty, and sales.Research methodologyIn terms of purpose, the current research is applicable, and of the survey research type. The statistical population of the research includes the customers of the food manufacturing and trading companies in the industrial towns of Ahvaz city. Due to the unlimited population, the statistical sample was considered to be 384 people using Cochran's formula, and finally 312 questionnaires were analyzed. Sampling in this research is available randomly. The collection tool in this research is a questionnaire.Research findingsData analysis was done using SPSS and PLS software. The findings showed that the identified factors had a significant effect, and the overall index of fit (GOF) was obtained as 0.661, which is a strong index and shows the overall high quality of the model.ConclusionThe present research was conducted with the aim of investigating the communication model of customer participation and competitive business with social media based on brand in manufacturing and trading companies. The results of this research is aligned with the results of Torki et al, (2023), Rahimi et al, (2023), Tang (2022), Shekarchizadeh & Hakim Akif Esfahani (2021), Dedeoglu (2019), Lee et al, (2019), Maia (2018), Taheri et al, (2017), Madrasi Tehrani & Saidi (2017), Esfandiari & Imankhan (2019). Rahimi et al, (2023) investigated the impact of digital content marketing on brand awareness through social media and customer interaction. The results showed that there is a positive and significant relationship between digital content marketing and brand awareness. Also, social media and customer interaction play a significant mediating role in the relationship between digital content marketing and brand awareness. It is obvious that digital content marketing as a new phenomenon plays a vital role in displaying brand name, strengthening customer relationship and increasing brand awareness, customer loyalty, and sales.In line with the obtained results, it is suggested:⮚ to improve the online activities of the company, the managers well provide the possibility of access to personal information for the customers and ensure the security of the customers' information.⮚ the managers provide the best information about products and services to customers through the company's websites.